2019
DOI: 10.1111/jsr.12859
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding practices and sleep development in pre‐schoolers from the EDEN mother–child cohort

Abstract: Sleep problems affect 20%–30% of toddlers and preschoolers. Few longitudinal studies focused on the impact of infant feeding practices on sleep. We aimed to study the associations between feeding practices up to 8 months and trajectories of sleep quantity or quality from 2 to 5–6 years. Analyses included 1,028 children from the EDEN mother–child cohort. Data were collected by self‐administered questionnaires. Associations between feeding practices (breastfeeding, complementary feeding, use of thickened infant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In very young infants, Macknin et al (1989) showed that feeding infants cereals in the bottle before bedtime was not associated with infant's sleep at age 5 weeks or 4 months. This lack of association was also observed in later infancy in the EDEN study, showing no association between the age of baby cereal introduction with sleep quantity or quality trajectories between age 2 and 5 years (Murcia et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…In very young infants, Macknin et al (1989) showed that feeding infants cereals in the bottle before bedtime was not associated with infant's sleep at age 5 weeks or 4 months. This lack of association was also observed in later infancy in the EDEN study, showing no association between the age of baby cereal introduction with sleep quantity or quality trajectories between age 2 and 5 years (Murcia et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
“…However, only 42% of the children achieved the protocol in the early introduction group. The EDEN mother–child cohort also showed that CFI before age 4 months was related to low risk of short sleep duration between age 2 and 5 years (Murcia et al, 2019). However, other studies found the opposite, with introduction of solid food before 4 months being associated with short sleep duration at age 1 (Nevarez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations